Doctor F.P. Haass and the police hospital as the first emergency hospital in Moscow - V. R. Kuchma; N. F. Plavunov; E. I. Shubochkina; V. A. Kadyshev (SINAPS LLC, 2019)
A brief description and the work field of the doctor and humanist F. P. Haass (Friedrich Joseph Haass), who came to Moscow as a family doctor and gave all his knowledge and medical art to his new homeland, is provided. His path is shown from a family practice to the organization of Moscow healthcare, the chief doctor and hospital builder, the organizer of prison medicine, the great philanthropist and humanist who cared for the poor and destitute. His sequence in the implementation of the idea of the need to organize the provision of ambulance and emergency medical care for the poor who were injured in the streets, frostbite, with fever, bitten by animals, etc, is shown. The work area of the Police Hospital, the characteristics of doctors - the main followers and successors of the work of F. P. Haass, a combination of their medical and scientific activities, contribution to medical science are presented. The history of the creation of the first Pasteur station in Russia to provide emergency care for bites of rabid animals is reflected. The role and merits of S. V. Puchkov in preserving the humanistic traditions of Dr. F. P. Haass in the Aleksandrovskaya (Police) Hospital, his achievements in preserving and perpetuating the memory of F. P. Haass, the opening of the monument to F. P. Haass at Maly Kazenny Lane, a large public activity of S. V. Puchkov in Moscow are shown. The importance of family traditions in the upbringing of dedicated medical service, which were followed by S. V. Puchkov's eldest son, A. S. Puchkov, is presented. Graduate of the Moscow University, A. S. Puchkov ("doctor with honors") continued the work of F. P. Haass and his father, proved to be a brilliant organizer and became the creator of the modern emergency care in Moscow that F. P. Haass had dreamed about.